Immunotherapy for Dogs: Still Running Behind Humans - Klingemann, Hans (Frontiers in Immunology, 2021)
Despite all good intentions, dogs are still running behind humans in effective cancer immunotherapies. The more effective treatments in humans, like infusions of CAR-T and NK-cells are not broadly pursued for canines due to significant costs, the rather complicated logistics and the lack of targetable surface antigens. Monoclonal antibodies are challenging to develop considering the limited knowledge about canine target antigens and about their mode of action. Although immunogenic vaccines could be less costly, this approach is hampered by the fact that cancer by itself is immuno-suppressive and any preceding chemotherapy may suppress any clinically meaningful immune response. This review – rather than providing a comprehensive listing of all available immunotherapies for dogs, aims at pointing out the issues that are holding back this field but which hopefully can be addressed so that dogs can “catch up” with what is available to humans.